Morphological rearrangement of the metabolic link of the microcirculatory bed of guinea pigs lungs after sensitization with ovalbumin - S. S. Popko (Zaporozhye State Medical University, 2021)
The reaction of the lung microvessels is an urgent issue of morphology and medicine in general, as well as one of the insufficiently investigated points in the study of morphological changes in chronic allergic diseases of the respiratory system. The aim is to study the morphological changes in the vessels of the metabolic link of the microcirculation in the lungs of guinea pigs sensitized with ovalbumin. Materials and methods. We have studied the lungs of 48 guinea pigs, using histological and morphometric methods, under conditions of experimental ovalbumin-induced allergic inflammation, simulated by three-time subcutaneous sensitization and subsequent 8-day intranasal inhalation of ovalbumin. To estimate the structural and functional state of capillaries, the inner diameter of the vessels was determined. Results. A general regularity in the reactivity of the hemomicrocirculatory bed of guinea pig lungs in experimental ovalbumin-induced allergic inflammation was established, which consists in a significant structural and functional restructuring of the exchange vessels of the microcirculatory bed. Dysfunction of the capillaries endothelium is manifested by a change of vasodilatation to vasospasm, as evidenced by morphometric changes in the diameter of the capillaries lumen in the experimental groups, and an increase in the permeability of the capillaries wall, which is confirmed by edema and disorganization of the connective tissue component. Conclusions. Allergic inflammation leads to structural and functional reorganization of the metabolic link of the hemomicrocirculatory bed of guinea pig lungs, which has a multidirectional staging character depending on the duration of the experiment and is a manifestation of a violation of the compensatory-adaptive processes of hemomicrocirculation. The most pronounced changes in the form of a decrease in the diameter of the lumen of the blood capillaries of the lungs of guinea pigs by 23 % compared to the control are observed during the late period of the development of the allergic inflammatory process.